MYOCARDIAL DYSFUNCTION IN SEPSIS PATIENTS - L. L. Plotkin; M. Yu. Rakhmanov; V. V. Kutubulatov (Вестник анестезиологии и реаниматологии)
Goal of the study: to study the frequency of myocardial dysfunction in sepsis patients and its impact on the outcome of the disease. Materials and Methods. 177 sepsis patients were enrolled into the retrospective cohort study. Myocardial dysfunction was diagnosed by transthoracic ultrasonic cardiography in 28% of patients. Results. According to the findings of the study myocardial dysfunction does not increase in-hospital mortality but increases the duration of artificial pulmonary ventilation (APV), vasopressor support and duration of stay in the intensive care department and general hospital stay. Reduction of left ventricle discharge less than 45% and increase of end diastolic size of the left ventricle are unfavorable prognostic factors for sepsis patients. Conclusions. Myocardial dysfunction is diagnosed in 28% of sepsis patients. Its development does not increase the rate of hospital mortality, but increases the duration of APV, vassopressor/inotropic support and duration of stay in the intensive care department and general hospital stay.